The review on Malaysian law regarding the rights of the aborigines on land matter in peninsular Malaysia / Intan Nurhidayah Zamridin...[et al.] - Zamridin, Intan Nurhidayah; Abdul Karim, Muna Najwa; Nazlan Ozizi, Nadia Amira; Mohamad Yazid, Siti Nur Naqia (Faculty of Law, 2013)
The study is carried out to review on Malaysian Law regarding the rights of the aborigines on land matter specifically in the Peninsular of Malaysia. The rights of the aborigines of Malaysia on land matters are stated in The Federal Constitution 1957 and The Aboriginal Peoples Act 1954. The issue focusses on whether The Federal Constitution 1957 and The Aboriginal People Act 1954 have sufficiently covered the rights of the aborigines of Malaysia on land matters. This research will cover on the aspects which these two Acts had failed to provide to the Orang Asli. One of the issue being discuss in on the amount of the compensation given to the Orang Asli upon their land being taken away. Besides the law, case law such as Sagong Tasi & Ors v Kerajaan Negeri Selangor & Ors [2002] 2 CLJ 543 and Adong bin Kuwau & Ors v. Kerajaan Negeri Johor & Anor [1997] 1 MLJ 418 will also be discussed. This research is based on the empirical research of the non-doctrinal research. The sources will be based on data gathered from various written sources and there will be interview sessions to be carried out. Thus, the research done has some recommendation proposed at the end of this research in view of improving the Acts and thereby provides a more comprehensive guideline